2017
DOI: 10.1371/journal.pone.0170673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Share 35 Rule on Waitlist and Liver Transplantation Outcomes for Patients with Hepatocellular Carcinoma

Abstract: IntroductionSeveral studies have investigated the effects following the implementation of the “Share 35” policy; however none have investigated what effect this policy change has had on waitlist and liver transplantation (LT) outcomes for hepatocellular carcinoma(HCC).MethodsData were obtained from the UNOS database and a comparison of the 2 years post-Share 35 with data from the 2 years pre-Share 35 was performed.ResultsIn the pre-Share35 era, 23% of LT were performed for HCC exceptions compared to 22% of LT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…A study evaluating the effect of "Share 35" on patients who underwent LT for HCC demonstrated no change in the proportion of LT performed or overall waiting time. However, a higher rate of death/de-listing was observed (20). Similarly, in our study, we did not observe any significant change in the rate of LT for HCC in the Share 35 era, although our study did not specifically evaluate UNOS regional differences.…”
Section: Author Manuscriptcontrasting
confidence: 52%
“…A study evaluating the effect of "Share 35" on patients who underwent LT for HCC demonstrated no change in the proportion of LT performed or overall waiting time. However, a higher rate of death/de-listing was observed (20). Similarly, in our study, we did not observe any significant change in the rate of LT for HCC in the Share 35 era, although our study did not specifically evaluate UNOS regional differences.…”
Section: Author Manuscriptcontrasting
confidence: 52%
“…This potential shift is congruent with the principle of using extended criteria organs in recipients with lower biological MELD scores, such as many HCC patients, because of the perception that these recipients are better able to tolerate an extended criteria organ [ 21 ]. A previous publication demonstrated that after the implementation of the Share 35 policy, more HCC patients have received livers from DCD donors [ 22 ], potentially as the result of the highest quality organs being preferentially utilized by higher MELD recipients with broader sharing.…”
Section: Changes To Allocation and Effects On Dcd Liver Transplantatimentioning
confidence: 99%
“…Historically, HCC patients have received a higher proportion of DCD donors than non‐HCC patients, which can be explained, in part, by an attempt to decrease wait‐list dropout for these patients, especially after the Share 35 rule was enacted. ( 29 ) However, in areas with organ shortages, wait‐list dropout rates for HCC patients are nearly 30%. ( 30 ) Expanding the pool of livers by using DCD donors has the potential to decrease this dropout rate, but properly selecting appropriate HCC candidates for DCD livers has been challenging.…”
Section: Discussionmentioning
confidence: 99%